Application of QuikSCAT radiometer rain rates to near-real-time global precipitation estimates: A global precipitation mission pathfinder - Ahmad, Khalil A.; Jones, W. Linwood; Kasparis, Takis (My University, 2004)
The SeaWinds scatterometer onboard the QuikSCAT satellite simultaneously measures the polarized microwave brightness temperature of the ocean/ atmosphere. QuikSCAT Radiometer (QRad) brightness temperatures are used to infer instantaneous oceanic rain rates using a statistical retrieval algorithm that has been developed using collocated QRad brightness temperatures with TRMM Microwave Imager (TMI) rain rate measurements. The algorithm produces earth-located instantaneous rain rate binned in 0.5 hour universal time windows and produced on a 50-km earth grid. The orbit of QuikSCAT allows independent rain temporal sampling that can be used to improve the estimation of global rainfall in 3 hour windows, which is a goal of the future Global Precipitation Mission (GPM). In this paper, QRad retrieved rain rate examples are presented and comparisons are made with the TRMM 3B42RT near real time product. Results demonstrate that QRad rain measurements agree well with these independent microwave rain observations and superior to the visible/infrared rain estimates, which demonstrates the utility of adding QRad to the 3B42RT product.